(untitled) (American Journal of Islam and Society, 2025)
This essay examines the historical and social context surrounding Mihajlo Mića Ljubibratić’s first translation of the Qur’ān into Serbian, published in 1895 in Belgrade. The article explores the political and social factors influencing Ljubibratić’s decision to undertake this translation, as well as the reception of his work in both Bosnia and Herzegovina and Serbia. It also discusses subsequent editions and publications of the translation. Additionally, the essay analyzes the Russian and French sources used in the translation and provides commentary on Ljubibratić’s stylistic choices within their sociolinguistic context.